Possible Traces of Early Modern Human Architectural Heritage: A Comment on Similarities Between Nest-Building Activity of Homo Species and Shelter Forms of Indigenous People in Sub-Saharan Africa - Hasan Basri Kartal; Mehmet Emin Şalgamcıoğlu; Asiye Nisa Kartal (Quaternary, 2025)
The architectural artefacts, materials, and techniques used for constructing shelters may share some common properties derived from the architectural culture that has evolved within the human species. This article examines the material features and settlement organisations employed in the nest-building activities of early human species and the shelter forms of indigenous peoples residing in sub-Saharan Africa. It questions whether early modern human notions of architectural heritage, which lack substantiation, might have influenced nest construction, typological differentiation, material utilisation, and the transmission of practices to subsequent generations and habitats. The focus is on home-based spatial organisation and the construction of structures. We recognise the need to clarify some fundamental misunderstandings regarding the nature of cultural and archaeological taxonomies, as well as the misuse of analogical reasoning when comparing contemporary hunter–gatherer populations with certain hominin groups. The paper aims to explore whether the early ‘Homo architecture’ in Africa bears any resemblance to that of modern Africans. The central inquiry of this study is whether indigenous architectural artefacts, materials, and techniques have been passed down throughout the evolution of architectural culture. The discussion suggests that the architectural products found in the settlement remains of early Homo species may exhibit characteristics similar to the huts of the indigenous people, who live as hunter–gatherers in sub-Saharan Africa. Discussing the architectural activities of different human species proves fruitful, as early architectural understanding and principles can be adapted to contemporary placemaking scenarios, urban design approaches, and housing models. We believe that, with further evidence, this foundational idea has the potential to be developed further.